2020
DOI: 10.3390/nano10020199
|View full text |Cite
|
Sign up to set email alerts
|

Eu-Doped Citrate-Coated Carbonated Apatite Luminescent Nanoprobes for Drug Delivery

Abstract: In the field of Nanomedicine, there is an increasing demand for new inorganic nanophosphors with low cytotoxicity and efficient loading-release ability of drugs for applications in bioimaging and drug delivery. This work assesses the potentiality of matured Eu-doped citrate-coated carbonated apatite nanoparticles to be used as theranostic platforms, for bioimaging, as luminescent nanoprobes, and for drug delivery applications, using Doxorubicin as a model drug. The drug adsorption isotherm fits the Langmuir–Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…The analysis of CSD and ζ-potential versus pH of aqueous suspensions of the nanoparticles is also relevant to assess their potential as luminescent probes in nanomedicine applications. The tendency of the colloid to disperse or aggregate in simulated physiological conditions in the blood (pH around 7.4) or in the tumor microenvironment (pH around 5-6) are related to the size and surface charge of the nanoparticles [16,46]. In addition, these features have an impact on the formation of the protein corona around the nanoparticles [47].…”
Section: Structural Physicochemical Morphological Characteristics mentioning
confidence: 99%
“…The analysis of CSD and ζ-potential versus pH of aqueous suspensions of the nanoparticles is also relevant to assess their potential as luminescent probes in nanomedicine applications. The tendency of the colloid to disperse or aggregate in simulated physiological conditions in the blood (pH around 7.4) or in the tumor microenvironment (pH around 5-6) are related to the size and surface charge of the nanoparticles [16,46]. In addition, these features have an impact on the formation of the protein corona around the nanoparticles [47].…”
Section: Structural Physicochemical Morphological Characteristics mentioning
confidence: 99%
“…Drug loading was followed by measuring absorbance of supernatant at 480 nm, before and after encapsulation using JASCO‐L‐670 spectrophotometer. Difference in absorbance gave the quantity of drug encapsulated [4,28] …”
Section: Methodsmentioning
confidence: 99%
“…dox‐loaded PEGylated polymer capsules were dispersed in 7 mL buffered saline of corresponding pH and aliquoted into seven equal fractions. Each fraction was centrifuged at various time periods and fluorescence of supernatant was measured (λ ex =480 nm; λ em =560 nm) [4,29] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to bioimaging, PLPs can also be used as drug carriers to construct a bioimaging-guided drug delivery system (Zhang D. et al, 2018 ). Previous studies have shown that folate-modified PLPs can precisely target tumor cells, so the researchers attempted to load the PLPs with anti-tumor drugs to treat tumors in situ (Jabalera et al, 2020 ). Shi et al synthesized the PLP probe Zn 1.1 Ga 1.8 Ge 0.1 O 4 :Cr 3+ ,Eu 3+ @SiO 2 with a 696 nm emission (Shi et al, 2015 ).…”
Section: Drug Delivery Based On Lanthanides-doped Plpsmentioning
confidence: 99%